Effectiveness of mRNA COVID-19 vaccine booster doses against Omicron severe outcomes - Grewal, Ramandip; Nguyen, Lena; Buchan, Sarah A.; Wilson, Sarah E.; Nasreen, Sharifa; Austin, Peter C.; Brown, Kevin A.; Fell, Deshayne B.; Gubbay, Jonathan B.; Schwartz, Kevin L.; Tadrous, Mina; Wilson, Kumanan; et al. (Nature communications, 2023)
We estimated the effectiveness of booster doses of monovalent mRNA COVID-19 vaccines against Omicron-associated severe outcomes among adults in Ontario, Canada. We used a test-negative design to estimate vaccine effectiveness (VE) against hospitalization or death among SARS-CoV-2-tested adults aged ≥50 years from January 2 to October 1, 2022, stratified by age and time since vaccination. We also compared VE during BA.1/BA.2 and BA.4/BA.5 sublineage predominance. We included 11,160 cases and 62,880 tests for test-negative controls. Depending on the age group, compared to unvaccinated adults, VE was 91–98% 7–59 days after a third dose, waned to 76–87% after ≥240 days, was restored to 92–97% 7–59 days after a fourth dose, and waned to 86–89% after ≥120 days. VE was lower and declined faster during BA.4/BA.5 versus BA.1/BA.2 predominance, particularly after ≥120 days. Here we show that booster doses of monovalent mRNA COVID-19 vaccines restored strong protection against severe outcomes for at least 3 months after vaccination. Across the entire study period, protection declined slightly over time, but waned more during BA.4/BA.5 predominance. This study investigates the protection provided by mRNA COVID-19 vaccine booster doses against Omicron-associated severe disease in adults aged 50 and older. The authors use data from Ontario, Canada, and find that booster doses provide strong protection but that it declined during the period of BA.4/BA.5 predominance.